The relationship between the thickness of the buccal and palatal cortical bone surrounding the maxillary third molars and the corresponding dimensions of the maxillary tuberosity: a retrospective cross-sectional study - Mohammed Amjed Alsaegh; Omar Almulla; Nawaf Almutairi; Bader Alkandari; Ahmad Altourah (BMC Oral Health)
Abstract Background Maxillary tuberosity and buccal plate fractures are common complications observed during routine extractions of upper third molars in daily dental practice. The study aimed to evaluate the association between buccal and palatal cortical bone thickness around upper third molars, the dimensions of the maxillary tuberosity, and the anatomical characteristics of the upper third molars. Methods This retrospective cross-sectional study analyzed 227 cone beam computed tomography (CBCT) scans retrieved from the archives of the University Dental Hospital of Sharjah (UDHS). Measurements included the buccal and palatal cortical bone thickness surrounding the upper third molars. The width, height, and length of the maxillary tuberosity were also evaluated, along with the anatomical features of the third molars. Data were analyzed using SPSS. Descriptive statistics, t-test, ANOVA, ANCOVA, and Pearson’s correlation were applied. Results The palatal cortical bone was significantly thicker than the buccal cortical bone (p = 0.011). The mean width, height, and length of the maxillary tuberosity were 8.78 ± 1.897 mm, 8.86 ± 3.262 mm, and 4.86 ± 1.490 mm, respectively. Males exhibited significantly greater mean tuberosity width and length compared to females (p < 0.001). Buccal cortical bone thickness positively correlated with tuberosity height (p < 0.001) and negatively with tuberosity width (p = 0.004). ANCOVA showed significant effects of root number (F = 3.107, p = 0.047) and age group (F = 2.854, p = 0.025) on buccal cortical bone thickness, with no significant interaction between gender and jaw side (p > 0.05). Additionally, a significant difference in tuberosity width (p = 0.002) was also observed across age groups. Furthermore, a positive correlation was found between tuberosity height and the root length of the associated upper third molar (p < 0.001). Conclusions The anatomical dimensions of the maxillary tuberosity and surrounding cortical bone of upper third molars were influenced by age, while sex affected only tuberosity dimensions. Additionally, correlations among upper third molar anatomy, cortical bone thickness, and tuberosity dimensions highlight the importance of thorough anatomical assessment and CBCT analysis to minimize surgical complications during upper third molar extractions.